Analysis of the Status and Influencing Factors of Online Learning - He, Jiaju; Zhao, Hong; Jiang, Fei (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
During the COVID-19 prevention and control period, large-scale online education was the largest digital transformation practice in education in human history. This study launched a questionnaire survey on primary and high school students. The survey was conducted from four aspects: demographics, online learning preparation, the online learning situations, and online learning experience. This study thoroughly investigated the status and problems of students’ online learning and analysed the characteristics of students’ online learning and the differences amongst grades. The study found that students have high adaptability and continuance intention to online learning.

(untitled)
Pendant la période de prévention et de contrôle du COVID-19, l'enseignement en ligne à grande échelle a été la plus grande pratique d'informatisation de l'éducation de l'histoire humaine. Cette étude a lancé une enquête par questionnaire sur les élèves du primaire et du secondaire. L'enquête a été menée sous quatre aspects : démographie, préparation à l'apprentissage en ligne, contexte de l'apprentissage en ligne et expérience de l'apprentissage en ligne. Cette étude a examiné de manière approfondie le statut et les problèmes de l'apprentissage en ligne des étudiants et a analysé les caractéristiques de l'apprentissage en ligne des étudiants et les différences entre les classes. L'étude a révélé que les étudiants ont une grande capacité d'adaptation et une intention de poursuivre l'apprentissage en ligne.